2007
DOI: 10.5194/acp-7-1333-2007
|View full text |Cite
|
Sign up to set email alerts
|

Detecting charging state of ultra-fine particles: instrumental development and ambient measurements

Abstract: Abstract. The importance of ion-induced nucleation in the lower atmosphere has been discussed for a long time. In this article we describe a new instrumental setup -Ion-DMPS -which can be used to detect contribution of ion-induced nucleation on atmospheric new particle formation events. The device measures positively and negatively charged particles with and without a bipolar charger. The ratio between "charger off" to "charger on" describes the charging state of aerosol particle population with respect to equ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 33 publications
2
96
2
Order By: Relevance
“…Yu (2006a) utilized a kinetically consistent ion-mediated nucleation model (IMN) to demonstrate that ions can lead to significant particle formation not only in the upper troposphere but also in the lower troposphere (including boundary layer). The role of ions in many boundary layer nucleation events has been recently confirmed by observations of evolving charged cluster distributions exhibiting significant overcharging in the nanometer size range during nucleation events (Vana et al, 2006;Hirsikko et al, 2007;Laakso et al, 2007). Nevertheless, the relative importance of ionmediated nucleation versus neutral nucleation under varying atmospheric conditions remains unresolved (Vana et al, 2006;Iida et al, 2006;Hirsikko et al, 2007;Laakso et al, 2007;Kulmala et al, 2007;Turco, 2007, 2008).…”
Section: Introductionmentioning
confidence: 77%
“…Yu (2006a) utilized a kinetically consistent ion-mediated nucleation model (IMN) to demonstrate that ions can lead to significant particle formation not only in the upper troposphere but also in the lower troposphere (including boundary layer). The role of ions in many boundary layer nucleation events has been recently confirmed by observations of evolving charged cluster distributions exhibiting significant overcharging in the nanometer size range during nucleation events (Vana et al, 2006;Hirsikko et al, 2007;Laakso et al, 2007). Nevertheless, the relative importance of ionmediated nucleation versus neutral nucleation under varying atmospheric conditions remains unresolved (Vana et al, 2006;Iida et al, 2006;Hirsikko et al, 2007;Laakso et al, 2007;Kulmala et al, 2007;Turco, 2007, 2008).…”
Section: Introductionmentioning
confidence: 77%
“…Some of the studies presented here indicate that the contribution from INU is just a few percent, compared to other nucleation mechanisms (Iida et al, 2006;Laakso et al, 2007). On the other hand there are also studies which point to ions as being a dominant source of new particles (Yu et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…In several observations (Vana et al, 2006;Iida et al, 2006;Laakso et al, 2007;Komppula et al, 2007) the charged fraction of the particles are used to evaluate the contribution of INU. Since particles nucleate below the limit of detection the charged fraction may change from the time of nucleation and until detection.…”
Section: Charged Fractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, campaign-wise observations indicate a connection between nucleation mode growth and ambient concentrations of monoterpenes (Laaksonen et al, 2008) -which is a dominant group of volatile organic compounds (VOCs) emitted by boreal forests. Direct measurements of particle composition have shown that most of the growth of particles in nucleation and Aitken mode size ranges (10-33 nm) may be due to oxygenated and/or nitrogen containing organics such as amines (Allan et al, 2006;Smith et al, 2008Smith et al, , 2010Barsanti et al, 2009), and indirect composition measurements suggest that significant fraction of also sub-10 nm particle mass may be organic (O'Dowd et al, 2002;Kulmala et al, 2007a;Riipinen et al, 2009). The comparison of the particle growth rates between the various studies, as well as analysis of the growth rates as a function of the particle size requires estimation of the accuracy of the determined growth rates, information which is rarely found in publications.…”
Section: T Yli-juuti Et Al: Growth Rates Of Nucleation Mode Particlmentioning
confidence: 99%